230k views
4 votes
Please I need the correct answer please

Please I need the correct answer please-example-1
User Sarme
by
5.4k points

1 Answer

4 votes

(−1

2 )(n^3)+

1

2 n^2+4.6n+(−

1

2)(n^3)+

1

2 n^2+4.5n

=

−1

2 n^3+

1

2 n^2+4.6n+

−1

2 n^3+

1

2 n^2+4.5n

Combine Like Terms:

=

−1

2 n^3+

1

2 n^2+4.6n+

−1

2 n^3+

1

2 n^2+4.5n

=(−1

2 n^3+

−1

2 n^3)+(

1

2 n^2+

1

2 n^2)+(4.6n+4.5n)

=−n^3+n^2+9.1n

Answer:

=−n^3+n^2+9.1n

Everything underlined means its a fraction/divided hope this helps :D

User Yoann Buzenet
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.